Pembinaan Mental Agama dalam Membentuk Perilaku Prososial - Khaeron Sirin (LPPM IAIN Sorong, 2017)
Religious mental development of the student is not started at Islamic boarding school (pesantren), but family. The family plays a very dominant. The child is born into the world begin to receive education and up bringing-educational treatments, starting from his parents, then from another family, all of which provide the basics of personality formation. The coaching of personality is supplemented and enhanced by Islamic boarding school. Religion becomes the controlling moral for someone. The religion should be included in the development of his personality and an inseparable element in personal integrity. If not included in his personal coaching, then the religious knowledge that will accomplish is science (science) who does not share control of behavior and attitude in life. Then will we will get intelligent people who are talking about the laws and the rules of religion, but not compelled to comply. The religious sense does not necessarily encourage people to act in accordance with that understanding. Maybe it happens and will look familiar, if we understand the dynamics of life and drives for every action. An action or attitude is the result of co-operation of all functions of the soul, which is covered in it understanding, feelings and habits. Similarly with religion, it will be a mental controller, if understood, perceived and familiarized (rational, emotional, and practiced).